Structures and energetics of BenCn (n = 1–5) and Be2nCn (n = 1–4) clusters - Fioressi, Silvina Ethel (2014)
The structures and energies of BenCn (n = 1–5) and Be2nCn (n = 1–4) clusters have been examined in theoretical electronic structure calculations. Cluster geometries were optimized in B3LYP/6-31G(2df) calculations and energies ordered in QCISD(T) calculations at the optimum geometries. Be and C bond to each other and to other atoms of their own kind, creating a great variety of low-energy clusters in a variety of structural types. Comparisons of the carbide clusters with previously explored silicide structures reveal some structural similarities, but the variety of carbide structures is much greater, owing primarily to the ability of carbon atoms to form multiple CC bonds.